Constructivism and technologies in education. Between innovation and learning to learn - Rubio Gaviria, David; Jiménez Guevara, Julián Ernesto (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of paper is to characterize the conditions of possibility of the discourse on constructivism in education, which is in turn a discourse that includes technology as one of its pillars. Originality / contribution: the work problematizes the meaning of the "knowledge society", questions the relationship between competences in education and innovation, as well as questions the discourse of "learning to learn" as the central issue of education that is assumed as constructivist. Method/ strategies Document review. Strategies: Thematic reading of documents on educational policy produced by international agencies. To conclude: it is proposed that constructivism became popular because it seems to reflect what is proposed around "the knowledge society" and the discourse on "learning needs" promoted by international agencies. In the same way, it is suggested that innovation is a structural condition of contemporary education, which explains the discourses of the development of skills and competencies, where it is not about learning something, but about learning to learn